Increase of the effectiveness of school PE classes through sport preferences survey: Contextual prediction of demanded sport activities - Michal Kudláček (Palacky University, 2013)
BACKGROUND: An effort to promote participation in any type of PA is more effective when it is aimed at needs, interests and preferences of particular target group. Current evidence emphasizes the insufficiency of PA in all age groups. OBJECTIVE: The purpose of the study was to analyze and describe the structure of sport activity preferences of high school students and to contribute to prospective improvement of sports and physical activity programs. METHODS: Two standardized questionnaires were used - 1. sport preferences questionnaire, 2. international physical activity questionnaire (IPAQ). The research sample (N = 333) consisted of high school students from the Czech Republic. RESULTS: Our results confirm that the differences between girls and boys are not as great as they were few decades ago. There is a visible dynamic in the development of sport preferences structure. Despite this fact there is a spectrum of sports that are constantly preferred - soccer, volleyball, aerobics and swimming. Acquired results indicate that the range of PA amount in girls varies from 2,372 MET-min/week (15 year old girls) to 4,467 MET-min/week (17 year old girls), while acquired results in boys varies from 2,535 MET-min/week (16 year old boys) to 4,973 MET-min/week (17 year old boys). The results, if properly applied, could increase the total amount of PA in high school students and improve the effectiveness of school PE.